Solutions For Growing the Power Factor Prevent A Reactive Electricity Tariff And Decrease Warmth On Installation With Bank Capacitors - Anggara Trisna Nugraha Angga; Muhammad Syahid Messiah; Dimas Rinaldi; Moch. Fadhil Ramadhan; Muhammad Jafar Shiddiq (Unusa Press, 2021)
PT. Intan Ustrix that's placed at Jl. Raya Roomo No.425, Sekarsore, Roomo, Kec. Manyar, Kabupaten Gresik Indonesia is a company engaged in the paper and cardboard business, and has many machines used in the manufacturing process. The load of the induction motor will make the cost lower, thereby increasing the current cost through the device inside the carton production unit. Fixing the cost of cos is a great way to solve this problem. In this case, it is very important to install a capacitor bank to recover the charge. By installing a capacitor bank will affect the overall performance of the motor used. The cause of this research is the increasing cost of boarding at the cardboard production unit of PT. Intan Ustrix. As an evaluation, capacitor banks are installed on the H200, AFG, 6PA, FM, and 6PS buses so that low cos costs can be increased. The final result of this charge shows that increasing the cos cost at full load of 325 KW from 0.716 to 0.872 can reduce the actual power cost (S) from 396 KVA to 329 KVA, which can maintain 65 KVA and today's decrease (I) from 498 A to 410 A, the lower the current consumption price of the motor used can increase the resistance of the device to the carton production unit.